Quasi-periodic eruptions as Lense–Thirring precession of super-Eddington flows - Middleton, M.; Gúrpide, A.; Kwan, T. M.; Dai, L.; Arcodia, R.; Chakraborty, J.; Dauser, Thomas; Fragile, P. C.; Ingram, A.; Miniutti, G.; Pinto, C.; Kosec, P. (Monthly Notices of the Royal Astronomical Society, 2025)
Quasi-periodic eruptions (QPEs) are a recently identified class of X-ray transient associated with tidal disruption events by supermassive black holes, and for which there are multiple possible explanations. In this paper, we present a simple model which requires the black hole be spinning, be misaligned with the accretion flow (both conditions of which are almost certainly met), and that the accretion rate is a few times the Eddington limit. We speculate that the resulting Lense–Thirring torques force the disc and entrained outflows to precess, leading to increased X-ray flux when the wind-cone is oriented at lower inclinations to the observer. We test the range of parameters for which this model could explain the period and brightness of the QPE events discovered thus far, and make qualitative comparisons between the observed X-ray spectra and light curves to those extracted from general relativistic radiation magnetohydrodynamic simulations. Overall, we find some areas of promising concordance, and identify challenges related to the details of current simulations.
CRIS-Team Scopus Importer:2025-02-14
Keywords: accretion; accretion discs; black hole; galaxies: active; neutron star mergers; relativistic processes; X-rays: galaxies